1H-NMR metabolomics investigation of CSF from children with HIV reveals altered neuroenergetics due to persistent immune activation - Thirion, Anicia; Loots, Du Toit; Williams, Monray E.; Solomons, Regan; Mason, Shayne (Frontiers in Neuroscience, 2024)
Background: HIV can invade the central nervous system (CNS) early during infection, invading perivascular macrophages and microglia, which in turn release viral particles and immune mediators that dysregulate all brain cell types. Consequently, children living with HIV often present with neurodevelopmental delays. Methods: In this study, we used proton nuclear magnetic resonance (1H-NMR) spectroscopy to analyze the neurometabolic profile of HIV infection using cerebrospinal fluid samples obtained from 17 HIV+ and 50 HIV- South African children. Results: Nine metabolites, including glucose, lactate, glutamine, 1,2-propanediol, acetone, 3-hydroxybutyrate, acetoacetate, 2-hydroxybutyrate, and myo-inositol, showed significant differences when comparing children infected with HIV and those uninfected. These metabolites may be associated with activation of the innate immune response and disruption of neuroenergetics pathways. Conclusion: These results elucidate the neurometabolic state of children infected with HIV, including upregulation of glycolysis, dysregulation of ketone body metabolism, and elevated reactive oxygen species production. Furthermore, we hypothesize that neuroinflammation alters astrocyte-neuron communication, lowering neuronal activity in children infected with HIV, which may contribute to the neurodevelopmental delay often observed in this population.